2012
DOI: 10.1371/journal.pone.0035312
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial and Smooth Muscle Cells from Abdominal Aortic Aneurysm Have Increased Oxidative Stress and Telomere Attrition

Abstract: Background Abdominal aortic aneurysm (AAA) is a complex multi-factorial disease with life-threatening complications. AAA is typically asymptomatic and its rupture is associated with high mortality rate. Both environmental and genetic risk factors are involved in AAA pathogenesis. Aim of this study was to investigate telomere length (TL) and oxidative DNA damage in paired blood lymphocytes, aortic endothelial cells (EC), vascular smooth muscle cells (VSMC), and epidermal cells from patients with AAA in comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
79
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 58 publications
(92 reference statements)
6
79
1
Order By: Relevance
“…Our results show unequivocally that human AAA-SMC exhibit a greater extent of DNA damage than non-aneurysmal SMC, in agreement with a previous study that also examined γH2AX and 8-dihydro-8-oxo-2′-deoxyguanosine as a marker of oxidative DNA damage [26]. However, in that study AAA-SMC were explored in situ in tissue sections or isolated as primary cells by a cytospin method without culturing [26]. It is notable that in early-stage PCA-SMC the presence of multi-nucleation was high in both VEH- and CCE-SMC alike.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results show unequivocally that human AAA-SMC exhibit a greater extent of DNA damage than non-aneurysmal SMC, in agreement with a previous study that also examined γH2AX and 8-dihydro-8-oxo-2′-deoxyguanosine as a marker of oxidative DNA damage [26]. However, in that study AAA-SMC were explored in situ in tissue sections or isolated as primary cells by a cytospin method without culturing [26]. It is notable that in early-stage PCA-SMC the presence of multi-nucleation was high in both VEH- and CCE-SMC alike.…”
Section: Discussionsupporting
confidence: 92%
“…We examined multi-nucleation (a feature of senescent and damaged cells [33,34]), deformation of normal ovoid nuclear morphology (more common in aged and DNA damaged cells [35,13]), and the presence of γH2AX (an early event in double-stranded DNA damage [36]). Our results show unequivocally that human AAA-SMC exhibit a greater extent of DNA damage than non-aneurysmal SMC, in agreement with a previous study that also examined γH2AX and 8-dihydro-8-oxo-2′-deoxyguanosine as a marker of oxidative DNA damage [26]. However, in that study AAA-SMC were explored in situ in tissue sections or isolated as primary cells by a cytospin method without culturing [26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is really hard to extrapolate an answer based on our current data, yet, it could be speculated that at least some of the changes involving either down or upregulation of genes can be explained by gross chromosomal changes that can be caused by MN and/or BN. In accordance with our findings, previous findings have indicated elevated oxidative DNA damage in other cardiovascular diseases, such as in the vessel wall of atherosclerotic plaques (Martinet et al, 2002), as well as in the endothelial cells and SMCs from AAAs (Cafueri et al, 2012). Hence, elevated genomic damage can be a common denominator in cardiovascular diseases and ROS appears to be a strong candidate responsible of this damage.…”
Section: Discussionsupporting
confidence: 92%
“…Endo III recognizes oxidized pyrimidines, including thymine glycol and uracil glycol. Consequently, both enzymes have been used as biomarkers of DNA damage caused by oxidative stress (21)(22)(23)(24). Our results showed that enzymatic digestion further increased genomic lesions caused by meglumine antimoniate, suggesting that DNA damage was induced by the oxidation of the nitrogenous bases of DNA.…”
Section: Discussionmentioning
confidence: 74%